2014
DOI: 10.1364/ao.53.000g12
|View full text |Cite
|
Sign up to set email alerts
|

Projection-type dual-view three-dimensional display system based on integral imaging

Abstract: A dual-view display system provides two different images in different directions. Most of them only present two-dimensional images for observers. In this paper, we propose a projection-type dual-view three-dimensional (3D) display system based on integral imaging. To assign directivities to the images, a projection-type display and dual-view screen with lenticular lenses are implemented. The lenticular lenses split the collimated image from the projection device into two different directions. The separated ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…In order to increase the viewing angle of the dual-view 3D display, we proposed a dual-view integral imaging 3D display using polarizer parallax barriers [17], but the resolution of each 3D image is reduced to half of the conventional one. In order to solve these issues, Seoul University proposed a projection-type dual-view 3D display based on integral imaging [19], but the display system is bulky. Then we proposed a dual-view integral imaging 3D display using an orthogonal polarizer array and polarization switcher [18], but the brightness is not high.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the viewing angle of the dual-view 3D display, we proposed a dual-view integral imaging 3D display using polarizer parallax barriers [17], but the resolution of each 3D image is reduced to half of the conventional one. In order to solve these issues, Seoul University proposed a projection-type dual-view 3D display based on integral imaging [19], but the display system is bulky. Then we proposed a dual-view integral imaging 3D display using an orthogonal polarizer array and polarization switcher [18], but the brightness is not high.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, an integral imaging-based DV 3-D display was proposed [20][21][22][23]. Wu and et al suggested a DV 3-D LCD system based on the lens array-based off-axis integral imaging method [19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, for the practical application of the 3-D DV display, two viewing-zones must be completely separated and have relatively large viewing-angles to experience the perspective changes of 3-D images. For this, J. Jeong et al proposed a projection-type DV 3-D display based on integral imaging [23]. They used a series of optical elements, such as a collimator, a lenticular lens with a vertical diffuser, and convex lens array for generation of a collimated beam, separation of DV images with enhanced viewing-angles, and integration of 3-D images to be displayed in their viewing zones, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second method, the elemental images are displayed on the left and right half of the display panel, but the 3D resolution of each 3D image is by half [12]. In the third method, the orthogonal polarizer arrays and the polarization switcher are used, the viewing zones and 3D resolution are the same as the conventional II 3D display, but it reduces the brightness and resolutionof the 3D images [13].In order to solve the above shortcomings,Seoul University has put forward a method [14].The lenticular lenses split the collimated image from the projection device into two different directions, although the reconstructed 3D images have high brightness, but the imaging quality has serious crosstalk, and the imaging quality is not good.…”
Section: Introductionmentioning
confidence: 99%